Diagnosis of Precocious Puberty in Girls - Gaudino, Rossella; Calcaterra, Valeria; Farello, Giovanni; Gasparri, Manuela; Monti, Claudio Maria; Bozzola, Elena; Villani, Alberto; Bozzola, Mauro (International Journal of Pediatrics and Child Health, 2020)
Puberty is one of the most astonishing periods of human life, when significant physical alterations occur along with psychosocial maturation. Precocious Puberty (PP) is defined as the appearance and progressive development of secondary sexual characteristics at a younger age than the general population, i.e. for Caucasian girls before 8 years of age. Untreated precocious puberty usually leads to short stature and can also cause significant emotional and behavioral issues. In recent years, an increased incidence of PP has been found in many countries although several studies now suggest that this trend has slowed down over the last decade in most industrialized countries, while persisting in other countries. Some girls with idiopathic precocious puberty may also have slowly progressive pubertal development without deterioration of their predicted height over a 2-year follow-up period. It is important to determine which girls to treat and the role of the clinician remains crucial. The clinician also needs to be familiar with the terminology of pubertal progression. The aim of this review was to examine the diagnosis of central precocious puberty (CPP) taking in account clinical practice and international literature.